Shakespeare uncovered - Hawke, Ethan, 1970-; Irons, Jeremy, 1948-; Jacobi, Derek; Denton, Richard; PBS Distribution (Firm); Blakeway Productions; 116 Films (Firm); WNET (Television station : New York, N.Y.) ([United States] : PBS Distribution, 2013)
Six episodes combine history, biography, iconic performances, new analysis, and the personal passion of their celebrated hosts (Ethan Hawke, Jeremy Irons, Derek Jacobi, Trevor Nunn, Joely Richardson, and David Tennant) to tell the story behind the stories of Shakespeare's greatest plays.
Macbeth -- Richard II -- Comedies : Twelfth night and As you like it -- Henry IV & Henry V -- Hamlet -- Tempest.
DVD, stereo. ; region 1, NTSC.
Subtitled for the deaf and hard of hearing.
Title from container.
Presenters: Ethan Hawke (Macbeth), Derek Jacobi (Richard II), Joely Richardson (Comedies), Jeremy Irons (Henry IV & V), David Tennant (Hamlet), Trevor Nunn (Tempest).
Originally broadcast as single episodes of a television program.
"This program contains material that may not be appropriate for all viewers. Viewer discrection is advised."
Keywords: Shakespeare, William, -- 1564-1616.; Dramatists, English -- Early modern, 1500-1700 -- Biography; European drama -- Renaissance, 1450-1600.; Video recordings for the hearing impaired; Documentary television programs